Prevention of Dementia Formation in Retired Combat Participants with a History of Traumatic Brain Injuries - Soloviev, Andrey; Ichitovkina, Elena; Golubeva, Elena (European Journal of Mental Health, 2020)
Background: A set of measures to prevent the formation of gross organic mental disorders in combat participants having traumatic brain injury (TBI) is an important public health task. This study aims to conduct a catamnestic survey of retired combat participants who possess a history of TBI to determine the directions of prevention of dementia formation.Methods: Seventy-one retired combatants were surveyed at the time of their retirement and three years after their retirement. Clinical and experimental psychological methods were used. To identify the dynamics of cognitive disorders, the Short Sample Test was used (in the adaptation of Vanderlick), and Kotenev’s Questionnaire of Traumatic Stress was used for post-stress disorders –. The catamnestic method was applied via the study of outpatient cards and using a social survey of retired combatants three years after their dismissal.Results: It was found that 47.8% of participants in combat operations had neurosis-like disorders with impaired emotions, 26.8% – organic emotional-labile disorder, 25.4% – organic personality disorder, 26.7% – alcohol abuse, and 25.4% were disabled due to mental illness. Three years after their dismissal, their cognitive abilities had a significant negative dynamic with a marked decrease in the integral indicator of intellectual activity; emotional disorders, and signs of psychosocial maladaptation were detected.Conclusion: A catamnestic analysis of the mental health of participants in combat operations with traumatic brain injury in their history showed the presence of adverse psychosocial trends, a fact that requires the development of measures to improve the effectiveness of complex inter-professional therapy and rehabilitation. To prevent the formation of deep mental disorders with severe cognitive impairment and dementia, it is necessary to develop and improve the regulatory legal and information base for organizing psychiatric care.